2021
DOI: 10.4236/jcc.2021.910001
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Effect of Artificial Intelligence Real Estate Forecasting Using Multiple Regression Analysis and Artificial Neural Network: A Case Study of Ghana

Abstract: To transition from conventional to intelligent real estate, the real estate industry must enhance its embrace of disruptive technology. Even though the real estate auction market has grown in importance in the financial, economic, and investment sectors, few artificial intelligence-based research has tried to predict the auction values of real estate in the past. According to the objectives of this research, artificial intelligence and statistical methods will be used to create forecasting models for real esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Leveraging insights from the literature review, we found it particularly compelling that the ANN model showcased the highest R 2 value, indicating the strongest fit among the array of models tested. This empirical observation is substantiated by previous work from scholars such as Mc Cluskey et al (2012), Renigier-Biłozor and Wi sniewski (2013) and Ge et al (2021), who extolled the virtues of ANN models particularly when grappling with large and intricate datasets. Thus, our findings echo the sentiment prevalent in the literature, underscoring the potential for machine learning techniques, such as ANN, to drive breakthroughs in modeling complexity.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Leveraging insights from the literature review, we found it particularly compelling that the ANN model showcased the highest R 2 value, indicating the strongest fit among the array of models tested. This empirical observation is substantiated by previous work from scholars such as Mc Cluskey et al (2012), Renigier-Biłozor and Wi sniewski (2013) and Ge et al (2021), who extolled the virtues of ANN models particularly when grappling with large and intricate datasets. Thus, our findings echo the sentiment prevalent in the literature, underscoring the potential for machine learning techniques, such as ANN, to drive breakthroughs in modeling complexity.…”
Section: Discussionsupporting
confidence: 60%
“…The potential of ANNs in real estate appraisal has been extensively investigated in various studies (McCluskey and Borst, 1997; Nguyen and Cripps, 2001; Limsombunchai et al ., 2004; McCluskey et al ., 2013; Nguyen et al ., 2015; Abidoye and Chan, 2016; Demetriou, 2017; Abidoye and Chan, 2018; Yacim and Bosho, 2018a, b; Zhou et al ., 2018; Wang and Li, 2019; Horvath et al ., 2021). Among these studies, it was observed that ANNs demonstrated superior performance compared to MRA when utilizing moderate to large data sample sizes (Nguyen and Cripps, 2001; Ge et al ., 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…An artificial neural network (ANN) is a biologically inspired computer algorithm designed to work in the same way as the human brain processes information [37]. It consists of a number of processing elements (or cells) which represent artificial neurons.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…Evaluation Index Data Fusion. Through the feature extraction method of association rules, the association rules are extracted according to the evaluation index data of mathematics teaching quality [22], and the phase space distribution W of big data is established, which can be regarded as a judgment matrix n × m. ρ q and Pðn i Þ are used to represent the characteristic distribution vector and probability distribution function, respectively, so as to realize the effective fusion of evaluation index data of mathematics teaching quality [23,24]. When constructing the regression analysis model of data, it is necessary to make statistical analysis on the data related to the evaluation index of mathematics teaching quality under the method of regression analysis and clarify the data association rules.…”
Section: Evaluation Of Mathematics Teaching Quality Based Onmentioning
confidence: 99%